Variations in nutritional content of key ungulate browse species in Sweden - Capoani, Leonardo (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2019)
Understanding variations in the nutritional content of key ungulate browse species is not an easy task. Overall, my study focused to understand seasonal variations in nutritional values, available to wild browsers, found in the main tree and shrub species present in Scandinavia. Water, neutral detergent fibre (NDF) and crude protein (CP) content of twelve different plant species (i.e. 8 belongs to tree whilst 4 to shrub) collected in two different location of Sweden were analysed. My experiment produced five main key findings. Firstly, overall seasonality variation was recorded in all three nutritional components analysed; CP and water decreased from summer to winter, whereas NDF increased. Broadleaved species were more affected than evergreen species. A different situation was found for evergreen, where the seasonal variation recorded was very small for some species (e.g. CP in pine and NDF in spruce) and non-existing for others (e.g. lingonberry, Labrador tea and juniper). Secondly, the seasonal NDF-CP ratio showed a negative correlation between the two nutrients only for broadleaf, while for evergreen species the seasonal NDF-CP ratio was not significant. Thirdly, most of the high protein content was primarily found in leaves of broadleaved species during the vegetative season. During winter, however, pine and Labrador tea showed higher values for CP than the ones found in broadleaved twigs. The fourth finding showed whether for some species the twig size affected the NDF and CP levels. Aspen, silver and downy birch increased their protein content with the increase of the diameter, while aspen, salix, rowan and silver birch raised the NDF levels with the increase of the twigs’ diameter. Finally, the fifth result concerned the habitat and latitude effect. No significant effect of habitat onto NDF and CP was found, while latitude affected water content and CP but not NDF.